Work-function tuning on analogue properties of junction-less strained DG-MOSFET - Salehuddin, Fauziyah; Kaharudin, Khairil Ezwan; Mohd Zain, Anis Suhaila (Taylor's University, 2023)
This paper discusses an extensive investigation on the influence of work-function (WF) tuning on analogue properties of the n-type junction-less strained double-gate MOSFET. The investigation on the device has been conducted with fixed level of input parameters operating in saturation mode by taking the dependency of analogue properties on the WF tuning into account. Numerical simulation was performed using industrial-based process/device simulator, Silvaco TCAD tools. The simulation results revealed that analogue properties of the device such as transconductance (gm), transconductance generation factor (TGF) and output conductance (gd), output impedance (ro) and intrinsic gain (AV) varies erratically as WF increases from 4.1 to 4.8 eV. However, the early voltage (VEA) of the device decreases with increase in WF of metal gate. Despite scaling the physical gate length to 6nm, the device exhibits decent analogue qualities with gm and AV values of 3.56 mS/m and 37.14 dB, respectively.